2015
DOI: 10.1002/dc.23382
|View full text |Cite
|
Sign up to set email alerts
|

TROP‐2 expression in papillary thyroid carcinoma

Abstract: TROP-2 is a type I transmembrane glycoprotein which is over-expressed in various malignancies, and is related to epithelial cell adhesion molecule (EpCAM), also called TROP-1, gp40, and KSA. In this study, we evaluated TROP-2 expression in papillary thyroid carcinoma (PTC) and compared it to other thyroid neoplastic and non-neoplastic lesions. Immunohistochemical (IHC) evaluation for TROP-2 was performed on 137 thyroid fine needle aspiration (FNA) cell blocks (CB) which included classic PTC (64), follicular va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
21
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 36 publications
(56 reference statements)
9
21
2
Order By: Relevance
“…Studies, except one, demonstrated that TROP-2 was negative in neoplastic and non-neoplastic benign thyroid tissues [15,16,17]. Addati et al reported TROP-2 positivity in 4 non-neoplastic thyroid tissues and 2 cases of follicular adenoma [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies, except one, demonstrated that TROP-2 was negative in neoplastic and non-neoplastic benign thyroid tissues [15,16,17]. Addati et al reported TROP-2 positivity in 4 non-neoplastic thyroid tissues and 2 cases of follicular adenoma [14].…”
Section: Discussionmentioning
confidence: 99%
“…TROP-2, which is expressed on normal levels in various normal tissues especially placenta, is related to tumor growth, tumor progression and the invasiveness of tumor cells [13]. Recently, there have been studies reporting that TROP-2 may be used in the differential diagnosis of follicular epithelial cell derived thyroid lesions [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…16 Few recent studies have examined the role of TROP-2 in diagnosing PTC. 6,11,12,15 However, there was no agreement on the scoring system or its exact positive cut-off value, since all studies used different methods for IHC evaluation (automated or visual assessment). Also they used different quality of antibodies (mono-or polyclonal antibody).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-Trop-2 monoclonal antibodies have been shown to kill uterine serous papillary carcinoma cells in vitro. 10,12 Recently, few studies have investigated the role of TROP-2 in diagnosing PTC and have reported that TROP-2 is a promising marker for identifying PTC. 12 These studies urged us to evaluate TROP-2 expression and its diagnostic utility on tissue histopathological specimens and cell block cytological sections of PTC cases as well as other thyroid nodules with follicular pattern including hyperplastic nodules, FA and follicular carcinoma.…”
Section: Original Articlementioning
confidence: 99%
“…The tumor-associated calcium signal transducer 2 (Trop-2) is a type-1 transmembrane protein. Although Trop-2 is overexpressed in a large variety of human epithelial carcinomas (1)(2)(3)(4)(5), its expression is minimal or restricted in normal tissues. Notably, elevated expression of Trop-2 is associated with more aggressive disease and poor prognosis in several cancer types (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%